Fotodynamická terapie jako nová perspektivní metoda lécby nádorových onemocnení--II. Prehled fotosenzitizérů - Zimcík, P; Miletín, M (Ceska a Slovenska farmacie, 2004)
Since the time when hematoporphyrine derivative (trade name Photofrin) has been introduced into clinical practice in Canada in 1993, a lot of new photosensitizers (PS) have been studied. Some of them successfully passed the clinical trials and are in use in the treatment of cancerous (ALA, temoporfin) and non-cancerous (verteporfin) diseases. The others (motexafin lutecium, talaporfin, phthalocyanines and SnET2) are entering or passing the clinical trials now. The newer PS are also called the second generation PS, when the first generation is composed of Photofrin only. The second generation PS usually possesses better properties, especially concerning absorption at longer wavelengths, shorter skin photosensitivity, better accumulation ratio between tumorous and healthy tissue and pharmacokinetics.
Keywords: fotosenzibilizující látky; Neoplasms; Photosensitizing Agents; fotochemoterapie; Humans; nádory; Photochemotherapy; lidé